Factors Affecting Clinical Learning of Undergraduate Nursing Students in Azad Jammu and Kashmir: Clinical Learning Experiences of Nursing Students - Nazar, Sofia; Zeb, Aurang; Idrees, Sobia; Sultan, Bushra (Pakistan Journal of Health Sciences, 2025)
Nursing education encompasses both theoretical knowledge and clinical education, equipping nursing students for their future roles and enabling them to transition from dependency to independent practice. Thus, clinical education is considered integral and irreplaceable in training nursing professionals, allowing them to attain various educational objectives, including enhanced communication skills and critical thinking. Objectives: To identify factors affecting the clinical learning of undergraduate nursing students in Azad Jammu and Kashmir. Methods: This quantitative descriptive cross-sectional design study collected data through a census sampling technique from 286 undergraduate nursing students. Inclusion criteria focused on students who attend at least one complete course of clinical rotation; students who were on leave or not willing were excluded from the study. Data was collected by using structured questionnaires, and analysis was made by using SPSS 26 version. Results: The findings revealed the challenges, such as inadequate supervision (42.7%), time constraints for nursing staff (82.2%), and student hesitation due to fear of errors (75.9%). Factors include hospital collaboration (71%), educator support (74.7%), and patient reluctance (71.7%). Correlation analysis links these factors to demographics, including supervision type and study year. Conclusions: The study findings concluded that clinical learning in nursing students is influenced by supportive environments, clear objectives, and adequate preparation, while barriers like poor supervision, discrimination, and lack of resources. These factors must be addressed through improved educator-student ratios, better training, and collaboration with clinical staff.